Adding effect sizes to a systematic review on interventions for promoting physical activity among European teenagers - Crutzen Rik (BMC, 2010)
Abstract This commentary adds effect sizes to the recently published systematic review by De Meester and colleagues and provides a more detailed insight into the effectiveness of interventions to promote physical activity among European teenagers. The main findings based on this evidence were: (1) school-based interventions generally lead to short term improvement in physical activity levels, but there were large differences between interventions with regard to effect sizes; (2) a multi-component approach (including environmental components) generally resulted in larger effect sizes, thereby providing evidence for the assumption that a multi-component approach should produce synergistic results; and (3) if an intervention aimed to affect more health behaviours besides physical activity, then the intervention appeared to be less effective in favour of physical activity.